PENGARUH SELEBRITI PENDUKUNG IKLAN MELALUI DAYA TARIK DAN KREDIBILITAS TERHADAP CITRA MEREK NUTRISARI OLEH MAHASISWA UNIVERSITAS 17 AGUSTUS 1945 (UNTAG) SURABAYA - Cempena, Ida Bagus; Febryono, Dheny (JEM17: Jurnal Ekonomi Manajemen, 2016)
This research title "Celebrity Influence Through Advertising Support Fascination And Credibility Against Brand Image NutriSari By August 17, 1945 University Students(UNTAG) Surabaya". Celebrity Supporters rent role as people talk about the product, whichwill influence the attitudes and behavior of consumers who indicate on the product supports.Celebrity supporters in the advertising ads is someone known to the public because of theirachievements in different fields of product classes are supported, such as the artist movies,soap operas, comedian, and all the famous people who are engaged in the field ofentertainment. The purpose of this study are: (1) To identify, analyze and prove whetherFascination and Credibility can simultaneously affect the brand image NutriSari By August17, 1945 University Students (UNTAG) Surabaya. (2) To identify, analyze and verify whetherFascination and Credibility can simultaneously affect the brand image NutriSari By August17, 1945 University Students (UNTAG) Surabaya. (3) To identify, analyze and prove thecredibility of Attraction and the most dominant influence on brand image NutriSari By August17, 1945 University Students (UNTAG) Surabaya. The hypothesis of this study are: (1)estimated Fascination and Credibility can simultaneously affect the brand image NutriSari ByAugust 17, 1945 University Students (UNTAG) Surabaya. (2) Anticipated Fascination andCredibility can simultaneously affect the brand image NutriSari By August 17, 1945University Students (UNTAG) Surabaya. (3) It is assumed Credibility most dominantinfluence on brand image NutriSari By August 17, 1945 University Students (UNTAG)Surabaya. This study proves that the Fascination and credibility significant effectsimultaneously Against Brand Image NutriSari By August 17, 1945 University Students(UNTAG) Surabaya. Fascination significant effect partially to the brand image NutriSari ByAugust 17, 1945 University Students (UNTAG) Surabaya. Significant effect partiallycredibility to the brand image NutriSari By August 17, 1945 University Students (UNTAG)Surabaya. Credibility is the dominant influence on brand image NutriSari By August 17, 1945University Students (UNTAG) Surabaya.Keywords: Celebrity Supporters rent, Attractiveness, Credibility, Brand Image.